How old are the oldest christian manuscripts? - Nongbri, Brent (The Biblical archaeology review, 2020)
The earliest Christian manuscripts are almost never dated explicitly, and scholars must rely on technical analyses and circumstantial evidence to establish probable dates. Learn about the uses and abuses of the dating techniques.